Investigation Into The Trends Consumption Of Carbohydrates Among Students In Second Cycle Institutions In Sunyani Municipality Of Ghana - Patience, Kyei; Comfort, Gyeduaah; Kwame, Ntow Gyan (Advances in Social Sciences Research Journal, 2015)
This paper focused on investigating into the consumption of carbohydrates among students in second cycle institutions in Sunyani Municipality Ghana. The specific objectives were to find out whether students in boarding houses have sufficient knowledge about carbohydrates, the types of carbohydrates students normally consume and the health related problems are associated with the types of carbohydrates they consume. A sample size of one hundred and twenty (120) respondents comprising of students, matrons and cooks was used. The stratified systematic random sampling procedure was used to select the sample and the study also employed the use of questionnaire as the main instrument for data collection. The results of the study revealed that, majority of the respondents have low knowledge about the types of carbohydrates and also consume more refined and processed carbohydrates foods like carbonated drinks, gari, sugar, sweets, biscuits, pastries, jam, pasta’s and candies. The study recommended that sustainable capacity building should be organized for matrons and cooks in second cycle institution in Sunyani municipality.